Analysis of mental state of athletes under pressure using electroencepahlograph (EEG) - Gao, P.; Ushiyama, Y.; Hori, J.; Akagawa, R.; Shioiri, A.; Kamijima, K. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
There is a close relationship between training and competition in all competitive sports. In this sense, the method of daily training is important to get good results in the competition. However, athletes experience often to fail to show their skill in the game which they have mastered in the training. Table tennis is the sport in which delicate control of small and light ball is decisive to win or lose the game. Even top players in the world make a simple mistake in the game. Such a mistake is related to psychology of the players. Thus, mental control is very important for athletes to keep good playing skill. If athletes follow reasonable training methods, they are able to improve the quality of training in the same psychological state as in the game. If regular patterns of players` psychology in normal practice are understood, it is possible to take advantage of the understanding to developing effective measures which enable players to adjust their mentality so that they can play the game with a good state of mind. The purpose of this work is to find that possibility based on brain waves measured by an electroencephalograph (EEG). In this work, influences on brain waves of coaching method and calling of coaches to players were investigated to see the mental state of players. To examine the changes of mental pressure in accordance with the scene of the play, a few cases were selected from the normal training program for the investigation. Case 1 is the one where a player is required to count the number of rally during the play and to hit the ball according to the instruction. The results of Case 1 showed that the player has higher concentration. Case 2 is the training of block defense against an offensive opponent. It was found in Case 2 that the player feels some modest pressure and tends to become nervous. It is expected to develop the training method which makes mental state in the training similar to that in the competition.